Is Gamekeeping in the Czech Republic an Institutionalized Form of Poaching? - Ambrožová, Zuzana (2011)
This paper aims at unveiling the true nature of the Czech hunting Act by modeling the competition for property rights characteristics among gamekeepers, the subsidized group, and other users of land based resources, the taxed group. We show that the subsidized gamekeepers' group seeking to decrease public opposition tries to obfuscate the true goal of its profit-oriented efforts by supporting relatively less revealing technically imperfect institutions. It does so by advertising artificially created qualities such as tradition and public interest. What hunters try to achieve technically is to shift the reference points of desire of the other users of land-based resources in order to disable them from perceiving total policy costs. As a result taxpayers' intrinsic advantage is undermined, and contrary to the efficient redistribution hypothesis a Pareto-inferior outcome is reached. Moreover taking full account of all costs of rent-seeking, including incomplete externality internalization, institutional rigidity and created moral hazard, total social costs, connected with the outcome of competition for property rights, are not minimized. Regarding empirical testing of the theoretical propositions, analyzing hunting statistics we prove that whereas the acknowledged public goals are not met, the technically imperfect Act 449/2001 Coll. creates moral hazard in favor of gamekeepers' private interests.